(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Analysis of the religious-political phenomena in the US culture is a new scientific and theoretical generalization. Civil religion in the United States from the point of view of Robert Bell, you can designate whether religion. The scientist does not study the divine and the human aspect of religion. R. Bell emphasizes that speak so – so indirectly pretend as if we already know that such a man, and that is God. Such a claim can not be scientific. The task of man to know as much as possible about the universe, including himself. This duty extends to all fields, including religion. Religion is based on reflective experience than specifically sensory experience. Religion is based on a religious experience. The difference between civil religion and traditional religion is that in the traditional religions of the people looking for personal salvation, why traditional religions define his private life. The civil religion a person gets a sense of its existence in society. Civil religion exists at the community level. P. Bella five-step classification was proposed, based on the degree of differentiation of religious symbols system was laid. Five stages have names: primitive, archaic, historic, modern. Key words: religious and political phenomenon, the culture of the United States, reflection, civil religion, the universe.